2018
DOI: 10.1080/0886022x.2018.1489288
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of sepsis-induced acute kidney injury in patients undergoing continuous renal replacement therapy

Abstract: Objective: The aim of this study was to investigate the clinical characteristics of sepsis-induced acute kidney injury (AKI) in patients undergoing continuous renal replacement therapy (CRRT).Methods: From 2011 to 2015, we enrolled 340 patients who were treated with CRRT for sepsis at the Presbyterian Medical Center. In all patients, CRRT was performed using the PRISMA platform. We divided these patients into two groups (survivors and non-survivors) according to the 28-day all-cause mortality. We compared clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
5
29
2
Order By: Relevance
“…The 28-day mortality of patients with CRRT was 62.5% in this research, matched for 62% in sepsis-induced acute kidney injury undergoing CRRT in previous reports [29].…”
Section: Discussionsupporting
confidence: 85%
“…The 28-day mortality of patients with CRRT was 62.5% in this research, matched for 62% in sepsis-induced acute kidney injury undergoing CRRT in previous reports [29].…”
Section: Discussionsupporting
confidence: 85%
“…Insufficient blood flow may be evident by low blood pressure, high blood lactate, or low urine output, which can eventually lead to kidney failure. In this case, we saw that the serum creatinine of the patient in both referrals reached above the normal and emergency dialysis was performed for him in the first time [9,10].…”
Section: Discussionmentioning
confidence: 86%
“…There several studies that had shown that the following factors: age, platelet count, APACHE II score, serum creatinine level, a urine output of <0.05 mL/kg/h the first day, eGFR <45 mL/min, et al were associated with the prognosis of patients with AKI undergoing CRRT [18,19]. Moreover, there was study that reported that BMI was a risk for AKI, but was not associated with prognosis of the patients with sepsis treated with CRRT [20].…”
Section: Discussionmentioning
confidence: 99%